Perubahan Frekuensi Nafas dan Suhu Tubuh Pasien Ketika Terjadi Serangan Asma - Hammad Hammad; Muhtar Muhtar; Syaiful Syaiful; Kurniadi Kurniadi (Poltekkes Kemenkes Mataram, 2022)
Assessment and risk reduction of asthma attacks is the main goal of nursing care for asthma attacks because it will be an important element in the management of therapy in patients. Clinical signs are often overlooked even though clinical signs must be monitored in detail to minimize the risk of increasing severity when an asthma attack occurs. Descriptive analysis is used to see the condition of the patient's breathing frequency and body temperature during an asthma attack. The population in this study used patients when they had an asthma attack in the emergency room by taking 70 respondents by simple random sampling. It was found that the respiratory frequency from the time of the asthma attack showed that the patient's mean respiratory rate was 31, the median was 30 and the mode was 28 with an SD of 5.8. The patient's body temperature was a mean of 37 C, median value 36.7, mode value 36.5 with SD 0.49. Serious monitoring of clinical signs of respiratory rate and body temperature is absolutely necessary for nurses to prevent an increase in severity during an asthma attack